2015
DOI: 10.1089/scd.2014.0076
|View full text |Cite
|
Sign up to set email alerts
|

Human Cerebrospinal Fluid Regulates Proliferation and Migration of Stem Cells Through Insulin-Like Growth Factor-1

Abstract: Mesenchymal stem cells (MSCs) and neural progenitor cells (NPCs) have been regarded for their clinical therapeutic potential for central nervous system (CNS) pathologies. Their potential utility is a result of their intrinsic ability to repair damaged tissues, deliver therapeutic proteins, and migrate to sites of pathology within the brain. However, it remains unclear whether the CNS promotes any changes in these potential therapeutic cells, which would be critical to understand before clinical application. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 58 publications
1
27
1
1
Order By: Relevance
“…1A, B, and C), we examined the PTEN protein in cells obtained from 16 GBM patients. Primary human fetal neural stem cells from two embryos were used as controls 17, 24, 37, 46, 53 . Primary cells obtained from nine patients (GBMs 612, 626, 651, 832, 965, 549, 922, 963, and 854) showed undetectable amounts of PTEN proteins.…”
Section: Resultsmentioning
confidence: 99%
“…1A, B, and C), we examined the PTEN protein in cells obtained from 16 GBM patients. Primary human fetal neural stem cells from two embryos were used as controls 17, 24, 37, 46, 53 . Primary cells obtained from nine patients (GBMs 612, 626, 651, 832, 965, 549, 922, 963, and 854) showed undetectable amounts of PTEN proteins.…”
Section: Resultsmentioning
confidence: 99%
“…reported that local delivery of IGF‐1 with PLGA/PEG microspheres has the potential to increase fat‐graft survival rates, which may further influence the cellular/stromal composition of the grafted tissue . It is also reported that IGF‐1 enhanced the migration, promoted proliferation, and inhibited apoptosis of hASCs …”
Section: Discussionmentioning
confidence: 98%
“…Cell migration was quantified using timelapse microscopy (Supplementary Movie 1). Long-term observation was done on a motorized inverted microscope (Olympus IX81) [47, 50, 51] equipped with a Cascade 512B II CCD camera and temperature and gas controlling environmental chamber. Phase-contrast and epifluorescent cell images were automatically recorded under 10X objective (NA = 0.30) using the Slidebook 4.1 (Intelligent Imaging Innovations, Denver, CO) for 15 h at 10–20-min intervals.…”
Section: Methodsmentioning
confidence: 99%